Trends in Global and Regional Integration by means of Trade - Iulia Monica Oehler-Șincai (Revista de Economie Mondială, 2014)
In the present paper we aim to emphasize several aspects of the economic integration realized through the channel of trade, from a double perspective. The first point of view is given by the formal framework, de jure, composed by the multitude of preferential trade agreements, while the second one, de facto, market-driven, is concretized by the global production networks. The first stance is exemplified through the agreements negotiated or concluded by the traditional trade powers, EU, US and Japan. Although, economically, EU is more present in Asia-Pacific than the US, the latter are politically more active and seem to gain ground. The second stance is underlined by means of the Asian integration specificity. East and South-East Asia represents the core of „Factory Asia” and is governed by the activity of the transnational corporations, their investment and cross-border networks, which makes the production process more fragmented and the regional economies more mutually dependent.